Analysis of snow-vegetation interactions in the low Arctic-Subarctic transition zone (northeastern Canada). (4th March 2017) - Busseau, Bruno-Charles; Royer, Alain; Roy, Alexandre; Langlois, Alexandre; Domine, Florent
Abstract: Recent studies have shown that northern vegetation has been growing in relation to a warming climate over the last four decades, especially across the transition zone between tundra and taiga. Shrub growth affects snow properties and the surface energy budget, which must be better studied to quantify shrub-snow-climate feedbacks. The objective of this research is to improve the characterization of the impact of shrubs on snow evolution, from its accumulation to its melt, using in - situ and satellite measurements. The research is presented for the Umiujaq site, Nunavik, representative of the low Arctic–Subarctic transition zone. Snow depth, measured along numerous transects spanning different land cover types is found to increase by a factor 2.5–3 between tundra and forest, while snow density decreases. This illustrates the trapping effect of vegetation well. Complementary, continuous snow depth measurements using weather stations from two sites (tundra with low shrubs and a small clearing with shrubs within the forest) show different site-dependent behaviors. Spatial analysis from high-resolution Pleiades images combined with Landsat (Normalized Difference Snow Index) and MODIS (Fractional Snow Cover) images suggest a slight delay in melt over open and dense forest areas compared to tundra and dense high shrubs.